2012
DOI: 10.4155/bio.12.89
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rp-Hplc Columns Used For Determination of Nucleoside Metabolic Patterns in Urine of Cancer Patients

Abstract: These results verify the usefulness of the RP-HPLC method to investigate the urinary pattern of normal and modified nucleosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The excretion of ribonucleosides is not affected by age and diet [2]. But elevated levels of ribonucleosides were observed in patients with physical illness, such as urogenital cancer [3,4], hepatocellular carcinoma [5,6], breast cancer [7], acquired immunodeficiency diseases (AIDS) [8,9] and severe combined immunodeficiency diseases (SCID) [10]. Therefore, the levels of urinary ribonucleosides can be considered as a signal of disease status, especially as potential biomarkers for cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The excretion of ribonucleosides is not affected by age and diet [2]. But elevated levels of ribonucleosides were observed in patients with physical illness, such as urogenital cancer [3,4], hepatocellular carcinoma [5,6], breast cancer [7], acquired immunodeficiency diseases (AIDS) [8,9] and severe combined immunodeficiency diseases (SCID) [10]. Therefore, the levels of urinary ribonucleosides can be considered as a signal of disease status, especially as potential biomarkers for cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the DEDC algorithm, the optimal gene set was nucleoside metabolic process (GO\GO:0009116) with Δ * G =18.681 and 24 HDE-HDC partitions in total. Nucleoside metabolic process refers to chemical reactions and pathways involving a nucleoside, a nucleobase linked to either β-D-ribofuranose (a ribonucleoside) or 2-deoxy-β-Dribofuranose (a deoxyribonucleoside), for example, uridine, inosine, guanosine, adenosine, cytidine and deoxyadenosine, deoxyguanosine, deoxycytidine and thymidine (44). Metabolic incorporation of azido nucleoside analogues into living cells enables sensitive detection of DNa replication through copper (I)-catalyzed azide-alkyne cycloaddition and strain-promoted azide-alkyne cycloaddition (45), whereas the altered DNa replications often lead to disease or even cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are no specific enzymatic systems to incorporate modified nucleosides into the macromolecular nucleic acid, these nucleosides once released cannot be reutilized, nor are they further degraded, but are excreted into the urine . Other studies also have demonstrated that urinary nucleoside excretion is little affected by the diet in humans, and when normalized to urinary creatinine levels, the daily excretion rate of urinary nucleosides is remarkably constant in healthy individuals . Thus, nucleoside detection could be useful in the assessment of human diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%